Peningkatan Produktivitas Tenaga Kerja Area Produksi Assy Air Cleaner di PT Astra Otoparts Divisi Adiwira Plastik - Widjaja, Willy Adi; Rahardjo, Jani (Jurnal Titra, 2013)
PT Astra Otoparts Adiwira Plastics Division (PT AO-AWP) is a manufacturing company engaged in the field of automotive components in Indonesia. One of its products is air cleaner which is manufactured in the assy air cleaner production area by utilizing man power in every line of the production. Continuous improvement system, which is the work culture, makes the company have an annual activity plan that must be achieved in order to make periodic improvements. One of the targets of this-year activity plan is enhancing the labor productivity of the assy air cleaner production area by 30%. Improvements to enhance the productivity can be identified and accomplished by analyzing the working conditions of man power, loading time, and takt time of the air cleaner products. The findings of the analysis showed some changes done such as working elements division, man power reduction in each line, supportive working tools creation, current working system improvement, and a new layout design to reduce the mobility of man power. The implementation of those improvements successfully increased the productivity by 65,43%, which implied that the annual activity plan target had been achieved.